Administrators' Gender Leadership Practices and Teachers'job Performance in Senior Secondary Schools in Kwara State - ETEJERE, Patricia A. O.; OLUWALOLA, Felicia K. (International Journal of Educational Management, 2021)
The leadership pattern of the school administrator shapes the tone of administration in the school system. Gender has been known to be a variable which may or may not influence the way schools are governed. This paper investigates administrators' gender leadership practices and teachers' job performance in secondary schools in Kwara State. Two research questions and five research hypotheses were used to guide the study. The research design adopted was the ex-post facto. A total of 118 principals and 324 teachers were selected as sample for the study from a total population of 118 principals and 1178 teachers in Ilorin South Senatorial District secondary schools.Two validated instruments namely: 'Administrators' GenderLeadership Practices Questionnaire' (AGLPQ) and 'Teachers' Job Performance Questionnaire (TJPQ) were used to gather data for the study. Reliability co-efficients obtained for the instruments were 0.83 for AGLPG and 0.77 for TJPQ respectively. Mean and frequency counts were used to answer the research questions while Pearson Product Moment Correlation statistics was used to analyze the hypotheses at 0.05 level of significance. The results showed that instructional supervision was the predominant administrators' leadership practice (3.42) while the level of teachers' job performance was high (3.35). The results further revealed that there was significant relationship between administrators' gender leadership practices and teachers' job performance. Among other things, the study recommended that school administrators in Ilorin South Senatorial District secondary schools should continue to make adequate use of administrators' leadership practices (such as instructional supervision, teamwork and strategic planning) in order to achieve the goals of the school system.